2006
DOI: 10.1159/000096095
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Interleukin-6 Genetic Polymorphisms and Levels of Autoantibodies to 60-kDa Heat-Shock Proteins

Abstract: Aims: Previously we reported an association between levels of anti-Hsp60 autoantibodies and interleukin-6 (IL-6) –174 SNP in Finnish population. The aim of this study was to investigate the same association in an independent population and to study four recently described SNP in IL-6. Materials and Methods: 313 healthy Hungarian subjects were recruited and genotyped for IL-6 –174(G→C), –9316(T→C), –1363(G→T), +1753(C→G), +2954(G→C). IgG antibodies to Hsp60 were measured by ELISA. LD between SNPs was computed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…the large inter-individual differences, is probably under the strict control and regulation of genetic factors. Our first observation obtained in a healthy Finnish population identified promoter polymorphism of interleukin-6 as one of the underlying regulatory factors (17), and these results were confirmed in a recent independent study (28). Furthermore, epistatic interaction between immunoglobulin GM allotypes and interleukin-6 was also identified in association with increased anti-Hsp60 antibody levels.…”
Section: Discussionsupporting
confidence: 77%
“…the large inter-individual differences, is probably under the strict control and regulation of genetic factors. Our first observation obtained in a healthy Finnish population identified promoter polymorphism of interleukin-6 as one of the underlying regulatory factors (17), and these results were confirmed in a recent independent study (28). Furthermore, epistatic interaction between immunoglobulin GM allotypes and interleukin-6 was also identified in association with increased anti-Hsp60 antibody levels.…”
Section: Discussionsupporting
confidence: 77%
“…A number of studies have focused on the role of interleukin-6 genetic polymorphism in inflammatory systemic diseases and conditions (17)(18)(19). There is strong evidence that genetic, as well as environmental factors affect the age of onset, severity, and risk of developing periodontitis (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the IL-6 genomic variants is associated with IL-6 levels to the susceptibility to many diseases (Kiszel et al, 2006;Talar-Wojnarowska et al, 2009;Yeh et al, 2010). Talar-Wojnarowska et al (2009) done a study with 97 pancreatic cancer or chronic pancreatitis patients and 50 healthy volunteers, and reported that IL-6 -174G/C gene polymorphism was correlated with circulating IL-6 levels and pathogenesis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%